Chitosan-Based Nano-Smart Drug Delivery System in Breast Cancer Therapy - Yedi Herdiana; Nasrul Wathoni; Dolih Gozali; Shaharum Shamsuddin; Muchtaridi Muchtaridi (MDPI AG, 2023)
Despite recent advances, cancer remains the primary killer on a global scale. Numerous forms of research have been conducted to discover novel and efficient anticancer medications. The complexity of breast cancer is a major challenge which is coupled with patient-to-patient variations and heterogeneity between cells within the tumor. Revolutionary drug delivery is expected to provide a solution to that challenge. Chitosan nanoparticles (CSNPs) have prospects as a revolutionary delivery system capable of enhancing anticancer drug activity and reducing negative impacts on normal cells. The use of smart drug delivery systems (SDDs) as delivering materials to improve the bioactivity of NPs and to understand the intricacies of breast cancer has garnered significant interest. There are many reviews about CSNPs that present various points of view, but they have not yet described a series in cancer therapy from cell uptake to cell death. With this description, we will provide a more complete picture for designing preparations for SDDs. This review describes CSNPs as SDDSs, enhancing cancer therapy targeting and stimulus response using their anticancer mechanism. Multimodal chitosan SDDs as targeting and stimulus response medication delivery will improve therapeutic results.